The Valley of Amazement - Tan, Amy (New York, NY : Ecco, an imprint of HarperCollinsPublishers, 2013)
Violet Minturn, a half-Chinese/half-American courtesan who deals in seduction and illusion in Shanghai, struggles to find her place in the world, while her mother, Lucia, tries to make sense of the choices she has made and the men who have shaped her.
Keywords: Americans -- Fiction -- China; Art -- Fiction; Courtesans -- Fiction; Family secrets -- Fiction; Identity (Psychology) -- Fiction; Kidnapping -- Fiction; Mothers and daughters -- Fiction; Shanghai (China) -- Fiction; San Francisco (Calif.) -- Fiction; Historical fiction